Effect of reducing sample volume on the detection of drugs in urine by transmission mode direct analysis in real time mass spectrometry. (6th February 2020) - Liang, Paul; Li, Frederick; Laramee, Brittany; Musselman, Brian
Abstract : Rationale: Matrix interference attributed to urea and other nitrogenous substances in unprocessed urine is significant. In this study desorption ionization of sub‐microliter volume samples is performed in an effort to improve the detection of drugs in unprocessed urine using transmission mode‐direct analysis in real time mass spectrometry (TM‐DART‐MS). Methods: Urine samples were spiked with analytical standards of two drugs of abuse, codeine and methadone. Various sub‐microliter volumes of unprocessed urine were deposited onto wire mesh screen consumables and analyzed using TM‐DART for desorption ionization and a high‐resolution mass spectrometer operated in full scan mode for mass analysis. A 2 2 factorial design of experiment (DOE) was employed to examine the effects of sample volume and sample introduction speed to the DART source. Results: Results from analysis of one microliter and sub‐microliter sample volumes were compared by measuring the signal produced by TM‐DART‐MS. Based on an α of 0.05, the lower‐volume samples yielded spectra where the abundance of urea and creatinine ions was reduced, thus significantly improving the TM‐DART‐MS signal for drugs of abuse. Using slower sample introduction speeds increased the time during which the sample was exposed to the heated ionization gas, resulting in a significant increase in the TM‐DART‐MS signal. Conclusions: Reducing the sample volume to sub‐microliter levels improved the detection of drugs of abuse present as either individual or multiple components of the untreated urine. The improved signal demonstrates the potential for using sub‐microliter volumes for screening drugs in urine without the need for chromatography or sample pretreatment.